Numerical Analysis of Mathematical Modeling with the Bisection Method in Finding the Roots of Complex Functions - Nurul Auliya, Silvana; Atikah Al Kudsiya (Etunas, 2023)
Mathematical modeling using the bisection method for finding complex function roots is a significant topic in numerical analysis. This research has a significant background as it focuses on solving complex function root problems, which play a crucial role in various scientific and technological applications. The objective of this research is to develop an efficient and accurate bisection algorithm to address the challenges in finding complex function roots. The research methodology includes mathematical modeling, numerical analysis, and implementation using the Python programming language. The research results demonstrate that the bisection method can effectively and efficiently discover complex function roots. We also present a Python implementation that can serve as a practical tool in real-world applications. In conclusion, this research finds that the bisection method is highly valuable for discovering complex function roots, providing accurate results and good convergence properties. The contribution of this research to the field of science is the development of an algorithm that can be applied across various domains, including simulation techniques, data analysis, and modeling complex systems.